EVALUASI TINGKAT KECEMASAN PADA PASIEN YANG MENJALANI TINDAKAN ANESTESI DI INSTALASI BEDAH SENTRAL RUMAH SAKIT UMUM PUSAT SANGLAH DENPASAR - Dwi Guna, Ni Kadek Saras; Suranadi, I Wayan; Senapathi, Tjokorda Gde Agung; Wiryana, I Made; Hartawan, I Gusti Agung Gede Utara (E-Jurnal Medika Udayana, 2025)
EVALUATION OF ANXIETY LEVEL IN PATIENTS WHO WILL RECEIVE ANESTHESIA IN CENTRAL SURGICAL INSTALLATION SANGLAH HOSPITAL DENPASAR   Background : Surgery and anesthesia could cause physiological and psychological stress which is expressed by patient as anxiety. Anxiety is one of the factors causing postoperative complications and it is a preventable condition. Objective : The purpose of this study was to know the level of anxiety and the factors that influence patient undergoing anesthesia at the Surgical Installation of Sanglah Hospital Denpasar. Methods : This study was conducted with an observational descriptive research design with cross-sectional approach and data is taken by total sampling. The subjects of this study were patients who would receive surgery and anesthesia at Central Surgical Installation. The research instruments included: informed consent, respondent's personal data, and Hamilton Rating Scale for Anxiety (HRSA) questionnaire. Results : The research subjects were 701 patients. Prevalence of anxiety in patients who will undergo anesthesia is 33,2%, 468 patients (66,8%) not experiencing anxiety, 90 patients (12,8%) mild anxiety, 61 patients (8,7%) moderate anxiety , 82 patients (11,7%) severe anxiety. Conclusion : Preoperative anxiety is a multifactorial event. The majority of patients do not experience anxiety. It is recommended to continue to improve the management and prevention of anxiety in a comprehensive manner.   Keyword : Anxiety Levels, Preoperative Anxiety, Preoperative, Anesthesia